Form and properties of the canonical Weierstrass product of an entire function with real values on R - Samoilenko, A. M. (Ukrains’kyi Matematychnyi Zhurnal, 2019)
UDC 517.2 We determine the form and properties of the Weierstrass canonical product of an entire function with real values on R. The proof of the theorem on the order of R-integral is specified [Samoilenko A. M. Order and canonical product of the Weierstrass R-integral // Ukr. Mat. Zh. — 2019. — 71, № 4. — P.564-570].